Endometrial hyperplasia process in female patients with chronic kidney disease: the choice of treatment tactics - Yu.E. Dobrokhotova; M.A. Lysenko; V.M. Grabovskiy; N.A. Shevchenko; N.P. Zapolskaya (LCC «Medicine-Inform», 2023)
Yu.E. Dobrokhotova1, M.A. Lysenko2, V.M. Grabovsky2, N.A. Shevchenko1,2, N.P. Zapolskaya2 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2City Clinical Hospital No. 52, Moscow, Russian Federation This article provides a literature review demonstrating modern paradigms concerning etiology, pathogenesis and management of endometrial hyperplasia processes in female patients with chronic kidney disease (CKD). Endometrial hyperplasia (EH) is a pathological process with various phenotypic cell changes and a characteristic predominance of glands over the stromal and epithelial components in the endometrium. Untimely diagnosis and treatment of EH can cause the pathology progression and the development of endometrium malignant transformation. Endometrial cancer (EC) refers to one of the most common malignant tumor forms of the female reproductive system, and EH, as a rule, is its precursor. In the gynecological morbidity structure, EH is 10 to 55%, and its incidence is steadily increasing. EH occurs as a result of excessive estrogen stimulation, when it is not compensated by the progesterone action. In addition, patients with CKD develop "immunosuppressive states" due to the use of various types of renal replacement therapy (hemodialysis, peritoneal dialysis, taking immunosuppressive drugs in patients with kidney transplant). Every year there are more and more such female patients. Over the past decade, there has been no reference in the Russian literature concerning a systematic approach to the diagnosis and treatment of EH in female patients with CKD. Considering that these were female patients of the reproductive period to a greater extent, who wanted to perform the childbearing function in the future, therefore, this problem is very relevant for the world medical community. Keywords: endometrial hyperplasia, abnormal uterine bleeding, chronic kidney disease, hemodialysis, kidney transplant, peritoneal dialysis, immunosuppression. For citation: Dobrokhotova Yu.E., Lysenko M.A., Grabovsky V.M., Shevchenko N.A., Zapolskaya N.P. Endometrial hyperplasia process in female patients with chronic kidney disease: the choice of treatment tactics. Russian Journal of Woman and Child Health. 2023;6(4):380-384 (in Russ.). DOI: 10.32364/2618-8430-2023-6-4-9.